REVEALING OPTIMAL FINANCIAL EFFICIENCY AND EFFECTIVENESS IN INDONESIAN VILLAGE GOVERNANCE - Purwanti, Dewi; Nurdini , Puji Nadiya; Suherman , Acep (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Effective financial management at the village level is crucial for achieving development goals and ensuring the optimal use of allocated resources. Specific Background: This study investigates the financial performance of Waringinsari Village, located in Takokak District, Cianjur Regency, West Java, through the lens of Value for Money (VFM) for the period 2021-2023. Knowledge Gap: Previous research lacks a comprehensive analysis of village financial performance using VFM indicators, particularly in the context of rural Indonesian governance. Aims: The primary objective of this research is to evaluate Waringinsari Village’s financial performance in terms of economy, efficiency, and effectiveness, and to provide recommendations for improving financial management practices. Results: The analysis reveals that Waringinsari Village performs